Relative rates of B meson decays into psi(2S) and J/psi mesons - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Aguilo, E; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; Alton, A; et al. (2009)
We report on a study of the relative rates of B meson decays into ψ(2S) and J/ψ mesons using 1.3fb-1 of pp̄ collisions at s=1.96TeV recorded by the D0 detector operating at the Fermilab Tevatron Collider. We observe the channels Bs0→ψ(2S), Bs0→J/ψ, B±→ψ(2S) K±, and B±→J/ψK± and we measure the relative branching fractions for these channels to be B(Bs0→ψ(2S))B(Bs0→J/ ψ)=0.53±0.10(stat)±0.07(syst)±0.06(B), B(B±→ψ(2S)K±)B(B±→J/ψK±)=0. 63±0.05(stat)±0.03(syst)±0.07(B),where the final error corresponds to the uncertainty in the J/ψ and ψ(2S) branching ratio into two muons. © 2009 The American Physical Society.